Fungicide evaluation against head smudge (Curvularia spp.) and its impact on yield and germination of tef (Eragrostis tef Zucc.) - Mekonnen, Mequanint Andualem; Nigusie, Walellign Zegeye; Emirie, Gebremariem Asaye; Hailemariam, Bogale Nigir; Abeje, Girmay Dires; Mekonnen, Melkamu Birhanie; Mihiretie, Aderajew (Informa UK Limited, 2024)
Head smudge, caused by Curvularia spp., is the major disease of tef in the humid tef-growing areas of Ethiopia. Despite this, farmers continue producing tef without any disease management strategies, which is leading to substantial quantitative and qualitative losses. Hence, the field and laboratory experiments were conducted to assess the efficacy of seven fungicides for the management of head smudge and simultaneously to assess the possible effects of the disease on seed quality of tef. The field experiment was conducted at Dangila and North Achefer districts and the treatments were arranged in a randomized complete block design with three replications. Tef seeds harvested from field experiments were subsequently used for laboratory studies using the blotter method and arranged in a completely randomized design. The effect of fungicides on reducing disease incidence and severity and increasing yield was significant (p < 0.001). The highest overall mean disease control (88.9%) was obtained from propiconazole sprayed plots followed by trifloxystrobin + tebuconazole and tebuconazole, both of which had a similar 85.5% disease reduction. The applications of triadimefon resulted in intermediate disease reduction (69.9%). However, the application of mancozeb + cymoxanil, cymoxanil + copper oxychloride, and thiamethoxam + metalaxyl + difenoconazole doesn’t bring a significant improvement from the untreated plot. According to our findings, head smudge can reduce tef yield by up to 62% and germination by 18.7 to 45.4%. Therefore, the application of propiconazole, trifloxystrobin + tebuconazole, and tebuconazole can be considered as effective head smudge management practice until other management options are developed.